2018
DOI: 10.1002/cne.24551
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐biased hippocampal pathology in the 5XFAD mouse model of Alzheimer's disease: A multi‐omic analysis

Abstract: Alzheimer's disease is a progressive neurodegenerative disorder and the most common form of dementia. Like many neurological disorders, Alzheimer's disease has a sex‐biased epidemiological profile, affecting approximately twice as many women as men. The cause of this sex difference has yet to be elucidated. To identify molecular correlates of this sex bias, we investigated molecular pathology in females and males using the 5XFamilial Alzheimer's disease mutations (5XFAD) genetic mouse model of Alzheimer's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 68 publications
8
60
0
Order By: Relevance
“…This result is largely consistent with other emerging findings of surprisingly poor correlation between mRNA and protein levels among a variety of experimental systems [13,17,[53][54][55], including analyses of human postmortem brain tissue [18,19,56]. In one notable study relevant to AD, a similar fraction (40%) of differentially expressed transcripts in the 5XFAD amyloid precursor protein transgenic mouse showed discordant changes in the proteome [57]. Many discordant changes likely reflect regulatory feedback interactions that maintain protein homeostasis.…”
Section: Discussionsupporting
confidence: 86%
“…This result is largely consistent with other emerging findings of surprisingly poor correlation between mRNA and protein levels among a variety of experimental systems [13,17,[53][54][55], including analyses of human postmortem brain tissue [18,19,56]. In one notable study relevant to AD, a similar fraction (40%) of differentially expressed transcripts in the 5XFAD amyloid precursor protein transgenic mouse showed discordant changes in the proteome [57]. Many discordant changes likely reflect regulatory feedback interactions that maintain protein homeostasis.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, even the youngest age group of 5XFAD mutant mice (3 months) displayed significant enrichment of genes containing 3' or 5' IREs compared to age-matched wild types. This is consistent with an enrichment of immune-related Hallmark gene sets that we observed in this age group (see Figure 7B) and with a previous transcriptome analysis suggesting immune activation in 5XFAD mice as early as 2-4 months [42]. UpSet plots of overlapping leading-edge genes suggest that the IRE responses due to aging and due to the 5XFAD transgenes may involve partially overlapping gene expression changes (Figure 8).…”
Section: Age-dependent Disruption Of Ire-driven Iron Homeostasis In Tsupporting
confidence: 91%
“…In the original paper characterizing Tg6799 (5XFAD) pathology [35], female mice demonstrated increased levels of Aβ 42 and Aβ 40 compared to males. Bundy et al showed that this may be due to increased expression of the transgene in female 5XFAD mice [39]. Females also appear to have increased BACE1 activity, a β-secretase processing enzyme which cleaves pAPP and produces pathogenic Aβ fragments [40,41], ultimately leading to increased amyloid plaque burden compared to male 5XFAD mice [41,42].…”
Section: Introductionmentioning
confidence: 99%